The current status of treatment of Wilms' tumor as per the SIOP trials - Jan Godzinski (Wolters Kluwer Medknow Publications, 2015)
This paper attempts to briefly describe the International Society of Paediatric Oncology (SIOP) policy of treatment of nephroblastoma since first study (SIOP 1) launched in 1971 until today. It focuses on the advantages of the preoperative chemotherapy and the stratification of patients induced this way. Marked efficacy of the pretreatment opened the way for less aggressive surgical management also in case of the "so-called" regular unilateral cases: Nephron-sparing surgery and minimal invasive techniques will probably find its place in this field of pediatric surgical oncology; however, very careful selection of cases must be the priority.